Znaczenie opozycji. Wokół pracy "Tonalność – ekspresja – semantyka. Studia nad pieśnią czasu modernizmu" Ilony Iwańskiej - Chwiłek, Agnieszka (Res Facta Nova, 2025)
The article is a review of Ilona Iwańska’s book Tonality – Expression – Semantics. Studies on the Song of the Time of Modernism (Akademia Muzyczna w Krakowie, 2020). The work is not a monograph on the issues of expression and semantics of tonality, but focuses on three selected aspects: opposition of modes (major vs minor); opposition of tonal melos (up vs down the circle of fifths - towards sharps vs towards flats); opposition of tonal-harmonic modes (cadential, in fourths and fifths vs alternating, in thirds). These structural oppositions are related to three semantic-expressive oppositions: joy and sorrow, brightness and darkness, necessity and possibility. The work is based on very rich theoretical and methodological foundations. The analyzed material consists of song cycles by Debussy, Strauss, Mahler, Berg and selected songs by Karłowicz, composed in the period from 1887 to 1908. The substantial summary of the considerations begins with a gallery of psychological portraits of the composers of the discussed songs. The author creates it by interpreting their tonal-expressive preferences and strategies. The key conclusions concern the way opposing pairs of categories function.